Integrasi Nilai-Nilai Surah Al-Insyirah dalam Membangun Manajemen Pendidikan Islam Berbasis Spiritualitas - Rahmawati, Aulia; Bustamam, Risman; S, Rinny (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This article explores the contribution of spiritual values ​​in Surah Al-Insyirah as a normative and practical foundation for Islamic education management. This Surah contains managerial principles that include mental readiness of leaders, workload management, integrity-based reputation building, sustainable productivity, and tawakal in decision making. This study uses a qualitative approach with a literature study method. The main data sources are obtained from classical tafsir books such as Tafsir Ibnu Katsir, Tafsir al-Maraghi, and contemporary scientific literature relevant to Islamic education management. Data collection techniques are carried out through systematic reviews of tafsir texts and academic journals. The data analysis technique uses content analysis to identify managerial themes contained in Surah Al-Insyirah. The results of the study indicate that Surah Al-Insyirah is very relevant as a guideline in building a resilient, spiritual, and divinely-oriented education management system